The Growth Response and Yield of Cucumber (Cucumis sativus L.) Fertilizing in Various Doses - Fitrianti Handayani; Maretik; Djunarlin Tojang; Mustafa R (Jurnal Biologi Tropis, 2023)
Cucumber plant (Cucumis sativus L.) is a vegetable plant that has many ingredients which can be used as vegetables, fresh vegetables, salads, or pickles and also cucumber plants can be beneficial for health. Production of cucumber plants in Indonesia from year to year has always decreased. The cause of the low production of cucumber plants in Indonesia is due to several factors, namely environmental factors, cultivation methods and also due to pests and diseases. This study aims to determine and understand the effect of organic and inorganic fertilizers on the growth and production of cucumber plants. The research design used was a randomized block design (RBD) consisting of 5 treatments repeated 3 times, namely 6 kg of goat manure/polybag (P0), 3 kg of goat manure/polybag + 2.5 g of NPK fertilizer/polybag (P1 ), 4.5 kg goat manure/polybag + 1.25 g NPK/polybag (P2), 1.5 kg goat manure/polybag + 3.75 g NPK fertilizer/polybag (P3), 5 g NPK fertilizer/ polybag (P4). The results of the analysis of the variety of application of organic fertilizer at a dose of 6 kg gave optimal results on plant height and number of fruit on cucumber plants but not on the number of leaves, age at the start of flowering, and fruit weight on cucumber plants.